2018
DOI: 10.1038/s41598-018-32758-8
|View full text |Cite
|
Sign up to set email alerts
|

Fasting-dependent Vascular Permeability Enhancement in Brown Adipose Tissues Evidenced by Using Carbon Nanotubes as Fluorescent Probes

Abstract: Brown adipose tissue (BAT), which is composed of thermogenic brown adipocytes (BA) and non-parenchymal components including vasculatures and extracellular matrix, contribute to the maintenance of body temperature. BAT distribution is detected by positron emission tomography-computed tomography (PET/CT) using 18F-fluorodeoxy glucose (18F-FDG) or single-photon-emission computed tomography-computed tomography (SPECT/CT) using [123/125I]-beta-methyl-p-iodophenyl-pentadecanoic acid. Although sympathetic nerve activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…In addition to the dense innervation of BAT, every brown adipocyte is also in contact with blood vessels, only separated by a basement membrane [ 43 ]. Fasting alters the endothelial basement membrane structure in BAT, resulting in increased transport into the intercellular space [ 51 ] as well as increased glucose uptake into BAT of humans [ 52 ]. This suggests that changes in the endothelial basement membrane in BAT can increase substrate delivery to brown adipocytes and thereby its activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dense innervation of BAT, every brown adipocyte is also in contact with blood vessels, only separated by a basement membrane [ 43 ]. Fasting alters the endothelial basement membrane structure in BAT, resulting in increased transport into the intercellular space [ 51 ] as well as increased glucose uptake into BAT of humans [ 52 ]. This suggests that changes in the endothelial basement membrane in BAT can increase substrate delivery to brown adipocytes and thereby its activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dense innervation of BAT, every brown adipocyte is also in contact with blood vessels, only separated by a basement membrane (Peirce V., 2016). Fasting alters the endothelial basement membrane (BM) structure in BAT, resulting in increased transport into the intercellular space (Yudasaka, Yomogida et al, 2018) as well as increased glucose uptake into BAT of humans (Vrieze A, 2012). This suggests that changes in the endothelial BM in BAT can increase substrate delivery to brown adipocytes and thereby its activity.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that CNTs coated with phospholipid polyethylene glycol (PLPEG-CNTs) provide images of BATs by a different mechanism. We showed that PLPEG-CNTs specifically extravasated from BAT capillaries and the extent of extravasation was augmented by fasting [ 65 ], suggesting that CNTs will provide an excellent tool for imaging BATs in accordance with their activities. Regarding CNTs, however, there are concerns in terms of safety for clinical usage.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%